Sundanese Ethnic Mentifact Culture Silih Asih, Silih Asuh, Silih Asah in the Context of Ethnopedagogy - Fatrah Taujiya Huzaeema; Ghaida Musabiha Nurvadi; Lintang Parameswari; Iin Wariin Basyari; Auliya Aenul Hayati (CV. AFDIFAL MAJU BERKAH, 2024)
Sundanese culture has various values and norms that are upheld by its people. One of the important concepts in Sundanese culture is silih asih, silih asuh, silih asah, which describes harmonious social relationships and mutual assistance between people. In the context of ethnopedagogy, the concept can play an important role in local wisdom-based education. This study aims to explore the Sundanese ethnic mentifact culture of silih asih, silih asuh, silih asah in the context of ethnopedagogy and to find out the implementation of silih asih, silih asuh, silih asah in elementary schools. This research focuses on how the concept of silih asih, silih asuh, silih asah can enrich and strengthen educational practices in Sundanese society. This research method uses a qualitative method of ethnography. The data collection techniques used are observation, interviews and documentation studies. The data analysis technique used is descriptive interpretative. The results showed that silih asih, silih asuh, silih asah, are still relevant and applied in the daily lives of Sundanese people. These values not only strengthen social ties but also have the potential to be applied in the world of education. In addition, it can help shape and improve the character of students who have empathy, tolerance, responsibility and enthusiasm for learning. In the context of ethnopedagogy, the values of silih asih, silih asuh, silih asah can be integrated into learning to create a more meaningful and local wisdom-based learning environment. The implementation of these values can help maintain and preserve Sundanese culture and improve the quality of learning.